DIGITAL ADVERTISING CONTENT ON SOCIAL MEDIA AFFECTS TOURISM PERCEPTION AND VISITING INTEREST - Sari, Novita; Saputra, Muhammad (FEB - Universitas Lampung, 2021)
This paper examines the content in the Wonderful Indonesia digital advertisement which is distributed through internet media, especially using YouTube channels and social media, whether they can influence the visiting interest of the people who are exposed to these advertisements. Visiting interest that arises is moderated by perceptions formed from the advertisements that are displayed. Advertising content contains elements of information, entertainment, as well as material that is considered disturbing the content of the advertising message. This study aims to examine whether the interest in visiting appears when looking at the three variables in the value of advertising and whether or not there is interest in visiting is mediated by the perception of the people who are exposed to the content of the advertising message.. This type of research is causality associative research. The population of this research is the people who are exposed to the Wonderful Indonesia version of tourism advertisements. The sampling method used purposive sampling method with certain criteria. The number of samples is 100 respondents. To analyze and test the relationship between the variables studied, the researchers used the full version of Lisrel software. The method in SEM Analysis consists of two approaches. The initial stage is the analysis of the measurement model that can show the latent variables measured by one or more observed variables. Furthermore, it can be seen its compatibility with the data. The second stage of causal relationship analysis is used to test the existing hypotheses in the study and draw conclusions. From the results of this study indicate that: elements of entertainment, elements of information, and elements of irritation affect the public's interest in visiting tourist attractions. There is no indirect influence of entertainment, information, and irritation on visiting interest through perception. Keywords: advertising, tourism, social media, perception, entertaining, information. JELL Classification : M31, M37, Z32